2018
DOI: 10.1080/02786826.2018.1511046
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of hydroperoxycarbonyls in secondary organic aerosol

Abstract: Highly oxidized multifunctional compounds (HOMs) formed through gas-phase reactions are thought to account for a significant fraction of the secondary organic aerosol (SOA) formed in low-nitric oxide (NO) environments. HOMs are known to be peroxide-rich and unstable in SOA, however, and their fate once they partition into particles is not well understood. In the study reported here, we identified particle-phase reactions and decomposition products for an a-alkoxy hydroperoxyaldehyde that served as a convenient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 50 publications
3
75
1
Order By: Relevance
“…Oxygen numbers of the products are generally lower than the original HOMs owing to, e.g., equations 1 and 2 of Scheme . We suggest that these processes, which could in principle occur in either the gas or particle phase, contribute to the difference between the particle phase product distribution in Figure and reported gas-phase distributions of HOMs. When viewed from the perspective of particle-phase chemistry, the mass spectrum in Figure provides evidence for substantial intermolecular reactivity within the particle phase, producing an interconnected oligomeric system. This reactivity may provide a molecular explanation for the high viscosity of the particle phase.…”
Section: Resultsmentioning
confidence: 92%
“…Oxygen numbers of the products are generally lower than the original HOMs owing to, e.g., equations 1 and 2 of Scheme . We suggest that these processes, which could in principle occur in either the gas or particle phase, contribute to the difference between the particle phase product distribution in Figure and reported gas-phase distributions of HOMs. When viewed from the perspective of particle-phase chemistry, the mass spectrum in Figure provides evidence for substantial intermolecular reactivity within the particle phase, producing an interconnected oligomeric system. This reactivity may provide a molecular explanation for the high viscosity of the particle phase.…”
Section: Resultsmentioning
confidence: 92%
“…22−28 Some of the decomposition is induced by heat, 22,23,25,26 while some occurs at room temperature on the time scale of hours. 27,28 These evidence suggest that certain oligomers in SOA are thermally unstable and might decompose or react under atmospheric temperature ranges, provided sufficient time. Simultaneously, particle-phase accretion reactions also take place, in which RH may play crucial roles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One prior study has shown that as the temperature cycles between atmospherically relevant set points, the SOA mass could not be reproduced, suggesting insufficient condensation/evaporation, or irreversible particle-phase reactions, or both . Growing evidence has demonstrated that atmospheric SOA could exist in distinct phase state and viscosity governed by RH, and do not always reach equilibrium upon evaporation and condensation. Further, common SOA constituents such as organic peroxides and some other types of oligomers were found to be labile and could decompose. Some of the decomposition is induced by heat, ,,, while some occurs at room temperature on the time scale of hours. , These evidence suggest that certain oligomers in SOA are thermally unstable and might decompose or react under atmospheric temperature ranges, provided sufficient time. Simultaneously, particle-phase accretion reactions also take place, in which RH may play crucial roles. It is thus imperative to determine how SOA chemical compositions transform, as the bulk and on the molecular level, under temperature and RH changes representative of the real atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary nitrates in a protic SOA environment could also act more generally as leaving groups, possibly promoted by the coproduction of HNO 3 in high-NO x experiments which could act as general acid catalyst, 52 leading to non-hydrolysis accretion reactions. D'Ambro et al 18 showed that the thermal desorption characteristics of high-NO x ipSOA, formed at low loadings (<2 μg m −3 ) was consistent with significant lowvolatility content that underwent thermal decomposition during desorption.…”
Section: ■ Model Overviewmentioning
confidence: 99%
“…Tertiary nitrates in a protic SOA environment could also act more generally as leaving groups, possibly promoted by the coproduction of HNO 3 in high-NO x experiments which could act as general acid catalyst, leading to non-hydrolysis accretion reactions. D’Ambro et al .…”
Section: Model Overviewmentioning
confidence: 99%